2018
DOI: 10.2355/isijinternational.isijint-2018-275
|View full text |Cite
|
Sign up to set email alerts
|

Mold Simulator Study of Effect of Mold Oscillation Frequency on Heat Transfer and Lubrication of Mold Flux

Abstract: The heat transfer and lubrication behavior of the slag film infiltrated into the mold/shell gap have a significant effect on the surface quality of continuous casting of steel slabs. With the mold simulator technique, the effect of mold oscillation frequency on the heat transfer and lubrication behavior of the infiltrated mold/shell slag film was studied in this article. The experiment results showed that the increase of the mold oscillation frequency from 1.00 to 2.00 Hz would cause the thickness of the infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…[13][14][15][16][17] This new modified distance (gap) between mould and shell affects significantly the heat transfer coefficient (HTC). [18][19][20] Thus, an inadequate combination of these factors increases the risk to form deep oscillation marks, which act as preferential sites for solid-state crack formation during bending and straightening in the secondary cooling zone. 21) Strain induced cracking in the secondary cooling is influenced by the shape changes of the strand, which results in tensile and compressive stresses that lower the ductility of the steel, as shown in Fig.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…[13][14][15][16][17] This new modified distance (gap) between mould and shell affects significantly the heat transfer coefficient (HTC). [18][19][20] Thus, an inadequate combination of these factors increases the risk to form deep oscillation marks, which act as preferential sites for solid-state crack formation during bending and straightening in the secondary cooling zone. 21) Strain induced cracking in the secondary cooling is influenced by the shape changes of the strand, which results in tensile and compressive stresses that lower the ductility of the steel, as shown in Fig.…”
Section: Identification Of Cracking Issues and Process Improvements Tmentioning
confidence: 99%
“…Sang-Hum KWON, 1,2) Young-Mok WON, 2) Gu Seul BACK, 1) Hyeju KIM, 1) Jae Sang LEE, 1) Dong-Gyu KIM, 3) Yoon Uk HEO 1) and Chang Hee YIM 1) * The unevenness of the solid-shell and heat flux (Φ q ) during solidification were measured for various steel grades with casting apparatus. Then the data were used to develop a model to predict the degree of solid-shell unevenness according to the steel composition.…”
Section: Prediction Model For Degree Of Solid-shell Unevenness During Initial Solidification In the Moldmentioning
confidence: 99%
“…Φ q in the specific carbon region is low due to air gaps that form as a result of peritectic transformation. [18][19][20] However, the solid-shell unevenness may not precisely coincide with Φ q of the mold, 21) because both phenomena are also affected by other factors including casting speed 21,22) superheat, 4,23) mold lubricant, 3,18,24,25) oscillation conditions and moldlevel fluctuation. 3,21,26,27) Some researchers have attempted to quantify the unevenness of solid-shell by measuring the solidification profile of steel according to the carbon concentration ([C]).…”
Section: Prediction Model For Degree Of Solid-shell Unevenness During Initial Solidification In the Moldmentioning
confidence: 99%
See 1 more Smart Citation
“…11) It was also reported that the rare earth oxides have a great effect on the melting temperature, viscosity, [12][13][14] structure [15][16][17][18][19] and crystallization 18,20) of mold fluxes. Specifically, the melting temperature and the viscosity property have direct influence on the lubrication between the solidified shell and the casting mold, [21][22][23] even the quality of the casting block. A appropriate value of viscosity is preferred to absorb inclusions and benefits the lubrication.…”
Section: Introductionmentioning
confidence: 99%